(untitled) (Stato, Chiese e pluralismo confessionale, 2021)
SUMARIO: 1. Enseñanza religiosa, identidad y ciudadanía - 2.- La nueva Ley de Educación - 2.1. Un cambio normativo con escasa participación ciudadana y durante una pandemia - 2.2. Los enfoques adoptados en la nueva Ley de Educación - 2.3.- El nuevo currículo basado en competencias - 3. Algunas cuestiones controvertidas sobre la enseñanza de la religión - 3.1. La ausencia de asignatura alternativa - 3.2. El valor de la asignatura de Religión en el expediente académico - 3.3. Enseñanza no confesional de Cultura de las Religiones - 3.4. Calendario de implantación de la LOMLOE y cuestiones pendientes de desarrollo reglamentario - 4. Consideraciones finales: Una reforma operada de espaldas a la sociedad civil. Religious Education, Identity and Citizenship. Regarding the Reform of the Spanish Education Law ABSTRACT: The aim of this paper is to analyze some issues raised by the teaching of religion in the Spanish legal system in the light of the current legislation in which some aspects of special relevance are modified. Specifically, it analyses the rejection generated by the absence of a mesured debate in which the most controversial aspects could have been discussed and a consensus reached, which would have required giving a more active role to the educational community and citizens. A proper approach requires, on the contrary, bringing together positions that truly balance the differents rights and guarantees at stake.